Improving Models of Income Dynamics using Cross-Section-Information - Robert Aebi; Klaus Neusser; Peter Steiner (Swiss Journal of Economics and Statistics, 2008)
Based on a relative entropy approach, this paper proposes a method to estimate or update transition matrices using just cross-sectional observations at two points in time. The method is then applied to explain the development of the US income distribution. Starting from three hypothesized transition matrices and a transition matrix estimated from the PSID data, we show how these matrices must be adjusted in the light of the cross-sectional information. Finally, we explore the consequences of these updated transition matrices for the future development of the US income distribution.
Keywords: D31; C51; 330; income distribution; income dynamics; relative entropy